2010
DOI: 10.4049/jimmunol.0903588
|View full text |Cite
|
Sign up to set email alerts
|

Herc5 Attenuates Influenza A Virus by Catalyzing ISGylation of Viral NS1 Protein

Abstract: Ubiquitin-like protein ISG15, which is robustly induced by IFN or virus, is implicated to inhibit influenza A virus (IAV) in vivo. But the underlying mechanism still remains largely unknown. In this study, we report that Herc5 could catalyze conjugation of ISG15 onto IAV-NS1 protein, the critical virulence factor of IAV. This modification produces two more species, respectively mapped to IAV-NS1 at lysine 20, 41, 217, 219, and 108, 110, and 126. The ISGylated IAV-NS1 fails to form homodimers and inhibits relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
136
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(140 citation statements)
references
References 62 publications
1
136
2
Order By: Relevance
“…Then, culture media was replaced by serum-free DMEM, and SeV, vesicular stomatitis virus (VSV), influenza A virus (IAV), or Newcastle disease virus (NDV)-GFP was added to the media at a multiplicity of infection of 0.2-1 according to specific experiments. After 1 h, the medium was removed, and the cells were fed with DMEM containing 10% FBS (32,33). Human H1N1 IAV strain IAV-PR8/34 was kindly provided by Dr. Ze Chen (Wuhan Institute of Virology, Chinese Academy of Sciences).…”
Section: Virus Manipulationmentioning
confidence: 99%
“…Then, culture media was replaced by serum-free DMEM, and SeV, vesicular stomatitis virus (VSV), influenza A virus (IAV), or Newcastle disease virus (NDV)-GFP was added to the media at a multiplicity of infection of 0.2-1 according to specific experiments. After 1 h, the medium was removed, and the cells were fed with DMEM containing 10% FBS (32,33). Human H1N1 IAV strain IAV-PR8/34 was kindly provided by Dr. Ze Chen (Wuhan Institute of Virology, Chinese Academy of Sciences).…”
Section: Virus Manipulationmentioning
confidence: 99%
“…The initial report identifying NS1 as an ISGylated protein indicated that ISGylation prevented the interaction of NS1 with importin-␣, a karyopherin essential for its nuclear import (30). A subsequent report described three additional roles for NS1 ISGylation: disrupting NS1 dimerization, preventing its interaction with PKR, and exhibiting an overall negative effect on NS1's ability to neutralize the IFN system (31).…”
mentioning
confidence: 99%
“…The NS1 protein undergoes three posttranslational modifications: phosphorylation by cellular kinases (4,12,13), ISG15 modification by the interferon (IFN)-induced ISG15 conjugation system (17,21), and modification by SUMO (11,20). It has been reported that these modifications affect the NS1 protein and the phenotype of the virus (4,17,21).…”
mentioning
confidence: 99%
“…It has been reported that these modifications affect the NS1 protein and the phenotype of the virus (4,17,21). Phosphorylation of threonines (Ts) of the NS1 protein was observed many years ago (12,13).…”
mentioning
confidence: 99%